Design and Verification of a Deep Rock Corer with Retaining the In Situ Temperature - Zhiqiang He; Heping Xie; Mingzhong Gao; Ling Chen; Bo Yu; Yunqi Hu; Jianping Yang (Advances in Civil Engineering)
Deep rock is always under high-temperature conditions. However, traditional coring methods generally have no thermal insulation design, which introduces large deviations in the guidance required for resource mining. Thus, a thermal insulation design that utilizes active and passive thermal insulation was proposed for deep rock corers. The rationale behind the active thermal insulation scheme was to maintain the in situ core temperature through electric heating that was controlled by using a proportional-integral-derivative (PID) chip. Graphene heating material could be used as a heating material for active thermal insulation through testing. In regard to the passive thermal insulation scheme, we conducted insulation and microscopic and insulation effectiveness tests for hollow glass microsphere (HGM) composites and SiO2 aerogels. Results showed that the #1 HGM composite (C1) had an excellent thermal insulation performance (3 mm thick C1 can insulate to 82.6°C), high reflectivity (90.02%), and wide applicability. Therefore, C1 could be used as a passive insulation material in deep rock corers. Moreover, a heat transfer model that considered multiple heat dissipation surfaces was established, which can provide theoretical guidance for engineering applications. Finally, a verification test of the integrated active and passive thermal insulation system (graphene heating material and C1) was carried out. Results showed that the insulating effect could be increased by 13.3%; thus, the feasibility of the integrated thermal insulation system was verified. The abovementioned design scheme and test results provide research basis and guidance for the development of thermally insulated deep rock coring equipment.